Reason for less water supply shortages under climate change condition: evaluation of future rainfall data - Jeong-Hyeok Ma; Chulsang Yoo; Wooyoung Na; Jong-Sub Lee (Journal of Water and Climate Change, 2023)
This study evaluates the appropriateness of general circulation model-based future rainfall data used in Korea. The evaluation is done through the analysis of long-term occurrence characteristics of dry years, as well as the analysis of the water supply system including the daily based rainfall-runoff analysis and reservoir operation. This study considers the Boryeong Dam basin in Korea as a study basin. Summarizing the results is as follows. First, the future rainfall data show that the occurrence frequency of dry years is similar to the observed, but the occurrence frequency of consecutive multi-year dry years is far smaller than the observed. Second, the future rainfall data result in no or far less water supply shortages. This is mainly due to the fact that the Boryeong Dam has the ability to overcome the one-year drought and the future rainfall data contain far fewer multi-year droughts. However, these results clearly indicate the problems of the future rainfall data, especially in the long-term persistence of rainfall. It is thus disappointing that these future climate rainfall data may not be used to evaluate the water supply system in the future, at least in the Boryeong Dam basin. HIGHLIGHTS The future rainfall data show more occurrence frequency of one-year droughts but far fewer multi-year droughts than the observed.; The future rainfall data result in no or far less water supply shortages.; This positive result is mainly due to the dam's ability to overcome the one-year drought and the future rainfall data with far fewer multi-year droughts.;